Phishing attacks discovery based on HTML layout similarity - Xue-qiang ZOU; Peng ZHANG; Cai-yun HUANG; Zhi-peng CHEN; Yong SUN; Qing-yun LIU (Tongxin xuebao)
Based on the similarity of the layout structure between the phishing sites and real sites,an approach to discover phishing sites was presented.First,the tag with link attribute as a feature was extracted,and then based on the feature,the page tag sequence branch to identify website was extracted,followed by the page layout similarity-HTMLTagAntiPhish,the alignment of page tag sequence tree into the alignment of page tag sequence branches was converted,this converted two-dimention tree structure into one-dimention string structure,and finally through the substitution matrix of bioinfor-matics BLOSUM62 coding,alignment score quickly to improve the phishing sites detection efficiency was computed.A series of simulation experiments show that this approach is feasible and has higher precision and recall rates.